Zero‐Thermal Quenching of Mn2+ Red Luminescence via Efficient Energy Transfer from Eu2+ in BaMgP2O7. Issue 23 (10th September 2019) - Shi, Rui; Ning, Lixin; Wang, Zhiqiang; Chen, Jiatang; Sham, Tsun‐Kong; Huang, Yan; Qi, Zeming; Li, Cuijin; Tang, Qiang; Liang, Hongbin
Abstract: Mn 2+ ‐activated phosphors usually show green to red luminescence depending on the crystal field strength in the lattice. However, the severe intensity loss of Mn 2+ luminescence at elevated temperatures remains to be a serious problem. Here, the observation of zero‐thermal quenching of Mn 2+ red luminescence (λem = 620 nm) up to 500 K in Eu 2+, Mn 2+ ‐codoped BaMgP2 O7 is reported. This phenomenon arises from an efficient energy transfer from sensitizers Eu 2+ which, when singly doped, exhibits a substantial thermal‐induced enhancement of 5d→4f emission intensity at 400 nm, along with a high luminescence efficiency and a large UV light absorption capacity. The present results open up a new path to the exploration of Eu 2+, Mn 2+ ‐codoped materials for thermally stable red phosphors. Abstract : A remarkable zero‐thermal quenching of Mn 2+ red luminescence is successfully achieved in Eu 2+, Mn 2+ ‐codoped BaMgP2 O7 material which arises from efficient Eu 2+ →Mn 2+ energy transfer and unique thermal‐induced enhancement of Eu 2+ luminescence in the system. The present results open a new gateway for developing thermally stable red phosphors.